PENGARUH BRAND EQUITY DAN BRAND EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DENGAN BRAND LOYALTY SEBAGAI VARIABEL MEDIASI PADA PRODUK IPHONE DI SURAKARTA - Arnindhita Divani Regita Putri; Aflit Nuryulia Praswati (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze the influence of brand equity and brand experience on consumer purchase decisions with brand loyalty as a mediating variable in Iphone products in Surakarta. The type of research used in the study uses quantitative methods. The population in this study is consumers who use Iphone products in Surakarta. Then, the sample used in this study is 100 respondents with the criteria of consumers who have used Iphone in Surakarta. This study uses primary data in its preparation. The data collection method used in this study is by distributing questionnaires online  through google forms. The data analysis technique in this study uses the Structural Equation Model (SEM) with Partial Last Square (PLS). The results of the study show that brand equity has a significant effect on consumer purchase decisions on Iphone products in Surakarta. Brand experience does not have a significant effect on consumer purchase decisions on Iphone products in Surakarta. Brand Experience has a negative effect on brand loyalty. Brand loyalty can mediate brand equity to consumers' purchase decisions on Iphone products in Surakarta. Brand loyalty can mediate the brand experience to consumers' purchase decisions on Iphone products in Surakarta